십이지장 주위 탈장 - 안상훈(Sang Hoon Ahn); 김지수(Jee Soo Kim); 장혁재(Hyuk Jai Jang); 조용필(Yong Pil Cho); 김용호(Yong Ho Kim); 김승용(Seung Yong Kim); 정승문(Seung Mun Jung); 한명식(Myoung Sik Han) (Annals of surgical treatment and research, 2002)
Paraduodenal hernia is a rare congenital anomaly caused by abnormal rotation of the midgut in embryonic stage, with part of the small intestine becoming trapped posterior to the mesocolon. Right and left paraduodenal hernias are distinct and separate entities, varying not only in anatomical structure but also in embryological origin. Paraduodenal hernia is a rare cause of acute intestinal obstruction. Careful clinical evaluation is needed for prompt surgical treatment. Because it is difficult to diagnose before exploration, and since paraduodenal hernia may cause potentially lethal complications such as obstruction, gangrene or bowel perforation, the possibility of internal hernia should be considered in any patient with acute intestinal obstruction who has no previous abdominal operation or external hernia. If paraduodenal hernia is suspected to be the cause of acute intestinal obstruction, the recommended tool for diagnosis is abdominal computed tomography. We experienced three cases of paraduodenal hernia, one case was right paraduodenal hernia while the others were left paraduodenal hernia. (J Korean Surg Soc 2002;62:348-351) KCI Citation Count: 1